THE IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION FOR STUDENTS' ORAL PROFICIENCY DEVELOPMENT - Rejeki, Astri (2014)
In many classrooms, the approach to teaching and learning is more unitary than differentiated. However, in reality, in a classroom every student is different. Each of them has their own learning characteristics and needs: different interest, readiness level, and learning style. In a classroom most teachers might not vary the learning content, product, and process based on the differences. Consequently, the students might not have optimal learning achievement. This classroom action research investigated how the students' oral proficiency might be improved through implementing the Differentiated Instruction. More specifically, the purpose of research was to find out what happens when students learn with Differentiated Instruction, and find out if the Differentiated Instruction can increase the students' learning achievement. This research used multiple data collection techniques: interview, classroom observation, and documentation. In addition, this study also administered a series of tests to check if students' learning was improving. The data were analyzed through weighing assessment rubric of oral proficiency, categorizing and coding the data, and calculating the students' learning Mean scores, Gained scores, and the Dependent t-test. Data under the research showed that the students learnt more effectively. Their oral proficiency was improving significantly. The students reflected a more comprehensive oral proficiency. It happened presumably because their learning characteristics and needs: learning styles, readiness level, and interest were better accommodated. In line with that, their Mean scores and Gained scores were also increasing. Furthermore, the tobserved was greater than tvalue, which means that the implementation of Differentiated Instruction in the classroom might successfully optimize the quality of students' learning. This finding showed a great potential that Differentiated Instruction might be used as an alternative way of improving students' learning.